Research on Pre-Competition Mood State of Sports Athletes and Their Individual Differences - Meiling Wang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
With the development of a country's economy and the progressive improvements in quality of life, sports and fitness are increasingly paid more attention. Regardless of the general sports and fitness-related needs, or the professional athletes who need a substantial amount of exercise, the scientific arrangement of exercise, training intensity and frequency, and monitoring of the athlete's mood state is an important topic. This paper uses bioelectric signals to study the mood state of male athletes during aerobic exercise, and analyzes the changes of the three signals of ECG, EMG and EEG in different physical mood states and the recovery period after exercise. This is done by constructing an objective recognition of the degree of mood state and the degree of recovery after exercise, while tracking and monitoring the changes of the athletes' red blood cell index, blood oxygen saturation, and heart rate indicators during the training process, to objectively evaluate the impact of the long-term training on the athlete's physical function, and provide suggestions for coaches to conduct scientific training. It is also hoped that further summarization of the variation rules of various physiological state evaluation indicators during long-term training of athletes will provide a certain technical support for athletes to avoid overtraining and damaging the body, and in doing so, scientifically restore their sports mood state.